2020
DOI: 10.1021/acs.accounts.0c00434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Photoswitching in Confined Spaces

Abstract: Conspectus In nature, light is harvested by photoactive proteins to drive a range of biological processes, including photosynthesis, phototaxis, vision, and ultimately life. Bacteriorhodopsin, for example, is a protein embedded within archaeal cell membranes that binds the chromophore retinal within its hydrophobic pocket. Exposure to light triggers regioselective photoisomerization of the confined retinal, which in turn initiates a cascade of conformational changes within the protein, triggering proton flux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 71 publications
0
96
0
3
Order By: Relevance
“…The curved Au particles were expected to facilitate both the interfacial reaction and the switching process. 43 45 …”
Section: Resultsmentioning
confidence: 99%
“…The curved Au particles were expected to facilitate both the interfacial reaction and the switching process. 43 45 …”
Section: Resultsmentioning
confidence: 99%
“…To date, the most extensive study in this field is the one performed by Klajn and coworkers. 90 First, they focused on surface-confined species and demonstrated that UV irradiation ( λ ∼ 365 nm) of ethynylanthracenyl-thiol immobilized on spherical Au NPs gave [4 + 4] dimerization, instead of the well-known selective [4 + 2] Diels–Alder reaction. The [4 + 2] vs. [4 + 4] selectivity could be tuned tailoring the curvature of the underlying NP surface, as well as the flexibility of the linker chains between gold and ethynylanthracene moieties.…”
Section: Reaction Vesselsmentioning
confidence: 99%
“…酰胺键之间的氢键增加了聚合物链的刚性 [30][31][32][33] , MC 之间的有序堆叠 [33] , 以及 MC 和酯−酰胺结构片段之 间的偶极-偶极相互作用 [15,17,[33][34] 进一步加强了抑制 MC 运动的效应. 我们把这种 MC 催化交联锁定自身 结构的策略称为 MC 的"自笼"化.…”
Section: P1cunclassified